Income inequality over the later-life course: A comparative analysis of seven OECD countries - Robert L. Brown; Steven G. Prus (Luxembourg Income Study (LIS), 2006)
This paper examines income inequality over stages of the later-life course (age 45 and older) and systems that can be used to mitigate this inequality. Two hypotheses are tested: Levels of income inequality decline during old age because public benefits are more equally distributed than work income; and, because of the progressive nature of government benefits, countries with stronger public income security programs are better able to reduce income inequalities during old age. The analysis is performed by comparing age groups within seven OECD countries (Canada, Germany, the Netherlands, Norway, Sweden, the United Kingdom, and the United States) using Luxembourg Income Study data. Both hypotheses are supported. Several conclusions are drawn from the findings.
Keywords: 330; Einkommensverteilung; Alte Menschen; Altersgruppe; OECD-Staaten; Kanada; Deutschland; Niederlande; Norwegen; Schweden; Großbritannien; USA